2015
DOI: 10.1093/occmed/kqu215
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fatigue on construction workers' physical and cognitive function

Abstract: Our results suggest an association between reported fatigue and experiencing difficulties with physical and cognitive functions in construction workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 24 publications
2
55
0
Order By: Relevance
“…Qualitative data have described negative effects from overtime work in construction including higher injury rates, lower productivity, and fatigue, and fatigue has been shown to influence construction workers’ physical and cognitive function . Our study found an association between mandatory overtime and lower health‐related productivity.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Qualitative data have described negative effects from overtime work in construction including higher injury rates, lower productivity, and fatigue, and fatigue has been shown to influence construction workers’ physical and cognitive function . Our study found an association between mandatory overtime and lower health‐related productivity.…”
Section: Discussionsupporting
confidence: 52%
“…It is likely that some effects of the work environment on work and health outcomes are mediated through changes in health behaviors; this question and others will be addressed with longitudinal follow‐up. For example, while a few studies in other industries have examined the additive effects of multiple workplace factors on worker health and well‐being, none have examined these relationships in construction, a workplace characterized by highly variable and changing work environments, nor have they examined the impact of these factors overtime. Our study was conducted among unionized carpenter and floor layer apprentices, who may not be representative of older workers, other construction trades, or nonunionized workers.…”
Section: Discussionmentioning
confidence: 99%
“…Construction work involves high-risk activities and requires physical and mental alertness among workers at all times [5]. In this study, the workers who felt fatigue tended to have complaints of physical and cognitive malfunctions [6]. Fatigue experienced by construction workers can be very dangerous because it can result in effects such as reduced concentration, poor decision making, failure in using work equipment and compromises on safety regulations; based on previous research, these effects are some of the determining factors and conditions (shaping factors) of workplace accidents [7,8].…”
Section: Work Fatiguementioning
confidence: 85%
“…Commonly cited precursors of physical fatigue include (a) heavy workloads, (b) awkward working postures, (c) prolonged working hours, (d) unstructured physical environment, and/or (e) dynamic work conditions (Lu et al, 2017; Yung, 2016). Physical fatigue has been observed in several U.S. industries: (a) advanced manufacturing, where 57% of manufacturing workers reported that they were fatigued over the past work week (Lu et al, 2017); (b) construction, where 49% of surveyed construction workers reported being “tired some days” and 10% “tired most days or every day” (Zhang, Murphy, Fang, & Caban-Martinez, 2015); and (c) fulfillment center order pickers, who pick 200 to 250 items per hour, walk approximately 6 miles per day, and have a 75% higher reported rate of musculoskeletal disorders (MSD) than the average employee (Schneider, Copsey, & Irastorza, 2010); this is a booming area of employment that is associated with e-commerce. It is important to note that the high prevalence of workplace fatigue is not limited to the United States alone; it has also been reported in Canada, the European Union, and Japan (Kajimoto, 2008; Loriol, 2017; Yung, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Van Amelsvoort, Kant, Beurskens, Schroer, and Swaen (2002) showed that fatigue was a strong precursor of future disability pension. Other workplace studies have shown significant associations between physical fatigue and (a) decreased physical and cognitive function (Zhang et al, 2015), (b) reduced short-term work capacity (MacIntosh, Svedahl, & Kim, 2004), (c) reduced leisure-time physical activity (Bláfoss et al, 2019), (d) diminished sensory motor coordination (Gage, 1974), (e) an increased likelihood of occupational deafness (Larsen, 1953), (f) reduced work performance (Barker & Nussbaum, 2011; Pasupathy & Barker, 2012), and (g) increased health-related complaints (Sluiter, De Croon, Meijman, & Frings-Dresen, 2003). The reader should note that these adverse health outcomes also lead to a substantial cost to both employers and health care systems (the aforementioned studies were conducted in Europe and North America).…”
Section: Introductionmentioning
confidence: 99%